Entrepreneurial learning from failure: a systematic review and bibliometric analysis on its theoretical foundations, antecedents, outcomes, and an agenda for future research - Asif, Iqbal; Mahani, Mohammad Abdu Shakur; Sharizal, Hashim; Muhammad, Asif (Springer Nature, 2025)
The purpose of this study is to provide an overview of the concept of entrepreneurial learning from failure (ELF), highlighting the different perspectives and factors associated with ELF and how entrepreneurs can learn from those experiences. This study uses a systematic literature review and bibliometric analysis to analyze research on ELF. Using Paul and Rosado-Serrano’s (2019) theory, characteristics, context, and methodology (TCCM) framework, the study summarizes the existing ELF literature. Therefore, this review synthesizes research on ELF theory development, context, characteristics, and methodology, aiming to assess the progression of literature development over time. Moreover, this systematic review examines the theoretical underpinnings, antecedents, and outcomes of ELF. The review synthesizes current research on this topic, identifies gaps, and proposes a future research agenda. A total of 65 peer-reviewed articles between 2000 and June 2023 were used in the analysis with VOSviewer version 1.6.20 to analyze data from the Scopus database. This study contributes to the existing literature on ELF in various ways. First, it analyzes field publication patterns by year, author, country, and institution. Second, it maps citation and co-authorship networks to find influential research and authors. Third, it maps the field’s intellectual structure by identifying prevalent themes and intellectual structures using co-occurrence and co-citation analyses, guiding academics to future study avenues and avoiding stagnation. Fourth, this study examines entrepreneurial learning from failure literature objectively and thoroughly using bibliometric analysis and systematic literature evaluation. Finally, we employed the TCCM framework to identify specific promising directions for further investigation.